95TH ANNIVERSARY OF THE CZECHOSLOVAK OPHTHALMOLOGICAL SOCIETY - Pitrová, Š; Řehák, J (Ceska a slovenska oftalmologie, 2022)
After the end of the First World War, the most important event in the history of our country was the establishment of the Czechoslovak Republic on October 28, 1918. Professor Deyl repeatedly spoke about the need to establish a Czechoslovak Ophthalmological Society. Only his successor, professor. O. Lešer implemented Deyl's idea and, in agreement with the heads of the Bratislava and Brno departments of ophthalmology, convened the opening general meeting of the Czechoslovak Ophthalmological Society on April 3, 1926, in the auditorium of the Czech department of ophthalmology with the participation of 37 ophthalmologists. Not all Czechoslovak ophthalmologists were present at this first meeting of the Czechoslovak Ophthalmological Society; their number can be estimated at about 55 in 1926. Immediately after the founding of the Czechoslovak Ophthalmological Society in 1926, a yearbook of congress works began to be published in the same year, every year until 1932, a total of 7 volumes. By the decision of the General Meeting of the Czechoslovak Ophthalmological Society, held on 15 May 1933, the publication of congress works was built on a new basis. The current form of the collection was abandoned, and the periodical journal Czechoslovak Ophthalmology was founded. In 1954, the Slovak branch of the ophthalmological section of the Czechoslovak Ophthalmological Society was founded, which quickly developed its activities and twice a year organized very successful and scientifically valuable congresses with rich participation and discussion. The name of the organization "Slovak branch of the Ophthalmological Section of the Czechoslovak Medical Society of J. E. Purkyně" was chosen. In 1969, under the Federalization Act, medical societies were reorganized; the Czech and Slovak Ophthalmological Society is established. The Federal Committee has since consisted of the chairs and secretaries of the two National Committees, who took turns in the leadership of the Federal Committee during their term of office. After the division of Czechoslovakia in 1993, the name of the magazine changed. Until 1994 it was published under the name Czechoslovak Ophthalmology and since 1995 the name has been changed to Czech and Slovak Ophthalmology. The first issue was published in February 1995, the continuity of the journal and the numbering has been preserved.
Keywords: Slovakia; Ophthalmologists; lidé; oftalmologie; Ophthalmology; Societies, Medical; Anniversaries and Special Events; oftalmologové; společnosti lékařské; Czech Ophthalmological Society; Humans; history; Slovenská republika; Slovak Ophthalmological Society; výročí a významné události; journal Czech and Slovak Ophthalmology